2015
DOI: 10.3109/02770903.2015.1072552
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of bronchial thermoplasty in patients with severe uncontrolled asthma

Abstract: BT is a cost-effective treatment for asthmatics at high risk of exacerbations. Continuing to follow asthmatics treated with BT beyond 5 years will help inform longer efficacy and support its cost-effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
2
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 23 publications
0
23
2
1
Order By: Relevance
“…Our results stand in contrast with those of Cangelosi et al . and Zein et al . who found BT‐OAT to be very cost‐effective relative to OAT (ICER of $US5495/QALY and $US29 821/QALY, respectively).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our results stand in contrast with those of Cangelosi et al . and Zein et al . who found BT‐OAT to be very cost‐effective relative to OAT (ICER of $US5495/QALY and $US29 821/QALY, respectively).…”
Section: Discussioncontrasting
confidence: 99%
“…and $US6690 in Zein et al .) . Moreover, the cost of an episode of exacerbation‐related hospitalization is roughly three times greater in the US compared with Singapore ($US9801 vs $US3340) while cost of an ED visit is nearly eight times higher ($US673 vs $US85).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study reported cost effectiveness of BT to be US$5,459 per quality-adjusted life year. A more recent study assessed the 10-year cost-effectiveness of BT for patients with severe uncontrolled asthma to be US$29,821 per quality-adjusted life year (22). When compared to the anti-IgE antibody therapy, omalizumab, a recent study demonstrated BT to be a potentially more cost effective option.…”
Section: Cost Effectivenessmentioning
confidence: 99%